Evaluation of the Effectiveness of Pneumococcal Conjugate Vaccines in Children - Woźniak, Kinga; Dachowska, Sandra; Fałczyńska, Aleksandra; Haraj, Jan; Namysł, Maria; Matczak, Simon; Bieniek, Maciej; Sobkowiak, Marcin (Journal of Education, Health and Sport, 2026)
Diseases caused by Streptococcus pneumoniae are one of the most common infectious causes of death worldwide, making them a major global burden. For this reason, pneumococcal conjugate vaccines (PCVs) are one of the key achievements in preventive medicine. PCVs are not only among the most widely used vaccines in the world but also have high clinical efficacy in preventing pneumococcal diseases, including invasive pneumococcal disease, meningitis, bacteremia, pneumonia, otitis media, and upper respiratory tract infections. In addition, PCVs contribute to herd immunity and reduce respiratory tract colonization with streptococci, particularly in newborns and infants, especially during the pre-vaccination period. Due to their very good safety profile, including a low risk of serious adverse reactions and high immunogenicity, PCVs are an important part of international and national vaccination programs. Nevertheless, their availability remains limited in low- and middle-income countries. The high replaceability and persistence of some serotypes, along with multi-drug resistance, keep Streptococcus pneumoniae infections as a major epidemiological challenge. This underscores the importance of monitoring variants and updating vaccination schedules. Modern PCVs now include more serotypes to combat these diseases, guiding future clinical research.